2009
DOI: 10.1124/dmd.109.030270
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Substrates for Human Cytochrome P450 2J2

Abstract: ABSTRACT:Several antihistamine drugs including terfenadine, ebastine, and astemizole have been identified as substrates for CYP2J2. The overall importance of this enzyme in drug metabolism has not been fully explored. In this study, 139 marketed therapeutic agents and compounds were screened as potential CYP2J2 substrates. Eight novel substrates were identified that vary in size and overall topology from relatively rigid structures (amiodarone) to larger complex structures (cyclosporine). The substrates displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 28 publications
(28 reference statements)
9
95
0
1
Order By: Relevance
“…34) Our results suggest that CYP2C9 plays a major role in AA metabolism in HLMs, consistent with a previous report. 8) Furthermore, our results indicate that CYP2C8 is also the key enzyme in AA metabolism in the liver, since the CR value of CYP2C8 was calculated to be over 30%.…”
Section: Discussionsupporting
confidence: 82%
“…34) Our results suggest that CYP2C9 plays a major role in AA metabolism in HLMs, consistent with a previous report. 8) Furthermore, our results indicate that CYP2C8 is also the key enzyme in AA metabolism in the liver, since the CR value of CYP2C8 was calculated to be over 30%.…”
Section: Discussionsupporting
confidence: 82%
“…This value is similar to the volumes found by Xia et al [23] (330Å 3 ) and Cong et al [22] (320Å 3 ) but notably smaller than those reported by Lafite et al [19] (945Å 3 ) and Lee et al [9] (1420Å 3 ). There are several potential reasons for this discrepancy.…”
Section: Generation and Validation Of A Homology Model For Human Cyp2supporting
confidence: 89%
“…can accept a wide range of xenobiotic substrates for detoxification [9][10][11]. Using screens of marketed therapeutic agents, albendazole, amiodarone, cyclosporine A, danazol, mesoridazine, nabumetone, tamoxifen, thioridazine, telmisartan and flunarizine were all shown to be potential xenobiotic substrates for CYP2J2.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of hydroxyalbendazole and hydroxyfenbendazole in HLM cultures were quantified using LC-MS/MS as described elsewhere, with some modification (2,11). The system consisted of a Thermo Vantage triple-quadrupole mass spectrometer (Thermo Fisher Scientific, San Jose, CA), coupled with a Thermo Accela HPLC system (Thermo Fisher Scientific).…”
Section: Chemicals and Reagents Hydroxyebastine Was Obtained From Tomentioning
confidence: 99%
“…1). Recently, Lee et al (11) reported that the rates of albendazole sulfoxide formation from albendazole by the recombinant CYP2J2 (rCYP2J2) isoform were significantly higher than those by the recombinant CYP3A4 (rCYP3A4) isoform, indicating the importance of the CYP2J2 isoform in albendazole sulfoxide formation (Fig. 1).…”
mentioning
confidence: 99%